KRETEK VILLAGE OFFICE GOODS INVENTORY INFORMATION SYSTEM BASED ON WEBSITE - Nabyla, Fuaida; Ihsani, M. Wildan; Syauqi, Achmad (STKIP Pesisir Selatan, 2023)
Managing inventory data is an important factor to think about. The amount and state of data might fluctuate due to routine data gathering activities. Consequently, the volume and complexity of these operations are beyond the capabilities of existing standard recording systems. To provide error-free access to inventory data, it is critical to record and maintain the data accurately. Computerisation has given effective online system-based solutions to these difficulties, thanks to technical breakthroughs. Even though they still used old-fashioned recording techniques, the Kretek village office was one of the first to use this technology. Efforts to handle inventories, outbound items, and loans have been greatly simplified by the new web-based information system. The system was built using PHPMyAdmin and the development technique was Prototype. Testing is conducted using Blackbox Testing and User Acceptance Test (UAT) to guarantee system performance and dependability, which is the goal of this study. This study employs a qualitative approach, drawing on information gathered via in-depth interviews and careful observation. Then, observation, interviews, and a review of the relevant literature were used as methods of data gathering. Comparing the two testing methods for this system, we find that Blackbox testing confirms that the application is functioning as expected and that all features and functions are functioning properly. On the other hand, UAT testing assigns values to each feature, so we see that the menu and features are good and acceptable, with 80% for display, 70% for application menu, 80% for operation process, 80% for convenience level, and 70% for percentage value.